1988
DOI: 10.1068/p170633
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of an Optical Flow Projected on the Ground Surface

Abstract: In most experiments in which the importance of visual control on postural stability is studied, optical stimuli attached to vertical surfaces are used. Analyses of long-term standing readjustments generally involve back-and-forth movements of a visual scene or its projection on vertical circular screens. In a natural environment, however, visual information is largely available from the ground. The aim of the experiment reported was to assess the effect of a flow pattern simulating an open outdoor setting on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…This point is of importance, as it has been established that flow structure is a determining factor in perceived (or induced) motion (Stoffregen, 1985). We have, in particular, shown that flows produced on the ground, such as those present during most common terrestrial displacements, may have a different perceptual status from textures flowing on vertical surfaces (Flückiger & Baumberger, 1988). In summary, it can be assumed that the visual characteristics of the scene produced by the TFG are very close to the natural geometrical optical structure encountered by a walker.…”
Section: General Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This point is of importance, as it has been established that flow structure is a determining factor in perceived (or induced) motion (Stoffregen, 1985). We have, in particular, shown that flows produced on the ground, such as those present during most common terrestrial displacements, may have a different perceptual status from textures flowing on vertical surfaces (Flückiger & Baumberger, 1988). In summary, it can be assumed that the visual characteristics of the scene produced by the TFG are very close to the natural geometrical optical structure encountered by a walker.…”
Section: General Methodsmentioning
confidence: 99%
“…The TFG was used to project a pattern of luminous dots on the ground (see Flückiger & Baumberger, 1988). The TFG was fixed on the ceiling and a number of circular holes were punched at regular intervals in a circular belt.…”
Section: General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Real visual environments used to study this phenomenon have been tilting rooms (Bles, Kapteyn, Brandt, & Arnold, 1980), rotating disks (Dichgans, Held, Young, & Brandt, 1972), and translating rooms (Bronstein, 1986;Lee & Lishman, 1975). Projected visual displays have simulated moving walls, tunnels, floors, and ceilings (Dijkstra, Schöner, & Gielen, 1994;Fluckiger & Baumberger, 1988;Lestienne, Schoechting, & Berthoz, 1977;van Asten, Gielen, & Diener van der Gon, 1988). Those experiments have shown that motion of a single surface background (in the simplest case, two dimensional) induces a codirectional postural sway.…”
mentioning
confidence: 99%